Hannah : The Complete Story - Hauxwell, Hannah, 1926- and Cockcroft, Barry (London Ted Smart, 1992)
A combined edition of "Seasons of My Life" and "Daughter of the Dales", telling the story of Hannah Hauxwell's life, from a remote Pennines' farm to life as a celebrity. She recalls her relations, friends and animals, along with the thriving community of Baldersdale in her youth
Include Color Illustration
Keywords: Hauxwell, Hannah, 1926- -- Manners and customs -- Women farmers